Transfemoral aortic valve implantation in severe aortic stenosis patients with prior mitral valve prosthesis - Sari, Cenk; Baştuğ, Serdal; Ayhan, Hüseyin; Kasapkara, Hacı Ahmet; Durmaz, Tahir; Keleş, Telat; Akçay, Murat; Aslan, Abdullah Nabi; Bayram, Nihal Akar; Bozkurt, Engin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Transcatheter aortic valve implantation for severe symptomatic aortic stenosis in patients with a previous mitral valve prosthesis is technically challenging, and pre-procedural comprehensive assessment of these patients before transcatheter aortic valve implantation is vital for an uncomplicated and successful procedure. Aim : We want to share our experience with transcatheter aortic valve implantation in patients with a preexisting functional mitral valve prosthesis and describe a series of important technical and pre-procedural details. Material and methods : At our center, 135 patients with symptomatic severe aortic stenosis were treated with transcatheter aortic valve implantation. Six of them with a preexisting mitral valve prosthesis received an Edwards SAPIEN XT valve through the transfemoral route. Results : Transcatheter aortic valve implantation was performed successfully in all 6 patients without any deformation of the cobalt-chromium/steel stents of the aortic valve bioprosthesis. Also no distortion or malfunction in the mitral valve prosthesis was observed after the procedure. There were no complications during the hospitalization period. Post-procedural echocardiography revealed no or mild aortic paravalvular regurgitation and normal valve function in all the patients. In addition, serial echocardiographic examination demonstrated that both the stability and function of the aortic and mitral prosthetic valves were normal without any deterioration in the gradients and the degree of the regurgitation at long-term follow-ups. Conclusions : Our experience confirms that transcatheter aortic valve implantation is technically feasible in patients with previous mitral valve replacement but comprehensive evaluation of patients by multimodal imaging techniques such as transesophageal echocardiography and multislice computed tomography is mandatory for a successful and safe procedure.